p53 Binding to Nucleosomal DNA Depends on the Rotational Positioning of DNA Response Element - Sahu, Geetaram (American Society for Biochemistry and Molecular Biology, 2010)
The sequence-specific binding to DNA is crucial for the p53 tumor suppressor function. To investigate the constraints imposed on p53-DNA recognition by nucleosomal organization, we studied binding of the p53 DNA binding domain (p53DBD) and full-length wild-type p53 protein to a single p53 response element (p53RE) placed near the nucleosomal dyad in six rotational settings. We demonstrate that the strongest p53 binding occurs when the p53RE in the nucleosome is bent in the same direction as observed for the p53-DNA complexes in solution and in co-crystals. The p53RE becomes inaccessible, however, if its orientation in the core particle is changed by ∼180°. Our observations indicate that the orientation of the binding sites on a nucleosome may play a significant role in the initial p53-DNA recognition and subsequent cofactor recruitment.